Effect of Financial Risk, Capital Structure and Banking Liquidity on the Profitability of Nepalese Commercial Banks - Rana, Sangita (Nepalese Journal of Finance, 2024)
This study examines the effect of financial risk, capital structure and banking liquidity on the profitability of Nepalese commercial banks. Return on asset and return on equity are selected as the dependent variables. Similarly, debt equity ratio, debt assets ratio, cash reserve ratio, credit to deposit, loan loss provision, non-performing loan and operational efficiency are selected as the independent variables. This study is based on secondary data of 16 commercial banks with 112 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, annual reports of the selected commercial banks and reports published by Ministry of Finance. The correlation coefficients and regression models are estimated to test the significance and importance of financial risk, capital structure and banking liquidity on the profitability of Nepalese commercial banks. The study showed that non-performing loans have a negative impact on return on assets and return on equity. It means that the higher the ratio of non-performing loans, lower would be the return on asset and return on equity. Likewise, there is a negative impact of operating efficiency with return on assets and return on equity. It implies that the increase in operating expenses leads to a decrease in return on assets and return on equity. Similarly, there is also a negative relationship of credit to deposit ratio with return on assets and return on equity. It indicates that increase in credit to deposit ratio leads to decrease in return on assets and return on equity. Further, loan loss provision has a positive impact on return on asset. This implies that increase in loan loss provision leads to increase in return on asset. However, cash reserve ratio has a positive impact on return on equity indicating that higher the level of cash reserve ratio, higher would be the return on equity of Nepalese commercial banks.